ORGANIZATION OF DENTAL CARE FOR UKRAINIAN CHILDREN DURING MARTIAL LAW - Koval, O.I.; Kaniura, O.A. (World of Medicine and Biology, 2024)
The war changed the lives of Ukrainians and presented them with new challenges. Not all children can receive proper medical, including dental care, at their place of residence due to constant shelling and systematic destruction of critical infrastructure. The humanitarian disaster has increased the risk factors for the growth of dental morbidity among children. This sets new tasks for the children's dental service to organize the provision of dental care to children under martial law in Ukraine. We have analyzed the dental care experience of children in Ukraine during martial law. We studied the organization and provision of medical and advisory assistance, including to children of Internally Displaced Persons; training in oral hygiene for children with disabilities, children of Internally Displaced Persons, low-income families, etc.; sanitary and educational work on the dental health of children among parents. Also, we access the Organization of Emergency Medical Care for children of Ukraine who were forced to cross the border, as well as the Organization of Humanitarian Assistance of medical direction directly to children (personal hygiene products, etc.) and medical institutions. In martial law, the priority is the choice of conditions for rehabilitating the oral cavity under general anesthesia, for the smooth operation of which strategic reserves of material and technical support are necessary.
Keywords: martial law; dental sanitation; children; general anesthesia; humanitarian aid